The role of asymmetric dimethylarginine (ADMA) in the follow-up of patients with precapillary pulmonary hypertension (PH). (25th November 2020) - Shafran, I; Probst, V; Campean, J; Sadushi-Kolici, R; Gerges, C; Lang, I; Skoro-Sajer, N
Abstract: Introduction: Asymmetric dimethylarginine (ADMA) interferes with L-arginine in the production of nitric oxide, a key mediator of endothelial cell function. ADMA is elevated in pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH) and is associated with unfavorable outcomes. Aim: To assess the role of ADMA to monitor disease progression of PH patients treated with PAH-specific therapy. Methods: ADMA was measured by competitive ELISA at baseline (BL) and follow-up (FU). Risk assessment including a clinical assessment, echocardiography, 6-minute walking test, NT-pro-BNP and hemodynamic assessment by right heart catheterization was performed accordingly. Risk was calculated according to the ESC/ERS 2015 guidelines by the SPHAR method. Results: ADMA samples were collected from 113 patients treated at our institution between 2012 and 2019. 89 (79%) patients had PAH, 15 (13%) were diagnosed with CTEPH and 9 (8%) with group 3 – PH associated with lung disease. 69% were females. 15 (13.3%) patients had a low risk at baseline, 96 (85%) intermediate risk and 2 (1.8%) were high risk patients. 75% received oral medications, 31% received subcutaneous treprostinil. Median baseline ADMA was 0.738umol/l. At BL no significant difference of ADMA plasma levels was found among the different PH types (p=0.063), or between different risk categories (p=0.531). Change in ADMA plasma levels correlated with change in risk (p=0.002, rs 0.291) and with change in mixed venous saturation (p=0.034, rs −0.205). Change in ADMA plasma levels also correlated with risk at FU (p=0.011, rs 0.240). Patients categorized as low risk at FU had a median ADMA plasma level decrease of 22%, compared with −3 to 0% ADMA plasma level change in patients with moderate to high risk at FU (p=0.04). Patients who improved their risk category had a median decrease of ADMA plasma level of 23% vs. 2.3% in patients who did not improve (p=0.011). Decrease of ADMA plasma levels was a weak but significant discriminator for improvement of risk in ROC analysis (p=0.032, AUC 0.374). Conclusion: ADMA plasma levels paralleled the hemodynamic and clinical benefit of PAH-specific treatments in patients with precapillary PH. ADMA could be used as a biomarker for monitoring treatment effects in precapillary PH. Funding Acknowledgement: Type of funding source: None